Hybrid treatment of thoracoabdominal aortic aneurysm: Case series and review of the literature - Zlatanović Petar; Končar Igor; Marković Miroslav; Trailović Ranko; Cvetić Vladimir; Davidović Lazar (Vojnosanitetski Pregled)
Background/Aim. Open thoracoabdominal aortic aneurysm (ThAAAs) repair is a challenging mission. Total endovascular approach is performed at selected institutions in developing countries, however these are not generalizable. Hybrid procedures offer an alternative approach. The aim of this study was to present our results of the ThAAA hybrid treatment and a literature review. Methods. This is a retrospective study of all patients that underwent the hybrid ThAAA repair at our institution between January 2011 and January 2018. Hybrid ThAAA repair was done as a twostaged procedure – open visceral debranching followed by stent-graft placement (TEVAR). The following data from eligible studies were extracted and analyzed: first author, publication year, patient sample, 30-day/in-hospital mortality, permanent paraplegia rate, presence of endoleaks and graft patency after the follow-up period, overall survival and mean follow-up period. Results. Seven patients underwent the hybrid ThAAA repair at our institution. Neither intraoperative death nor technical failure due to TEVAR was observed. Mean follow-up rate after discharge was 51.71 months [95% confidence interval (CI): 14.67–88.74 months]. At the time of the follow-up, all bypasses were patent and no prosthesis migration was documented. After one year, a case of type Ib endoleak was identified and treated successfully. Twenty-five studies were eligible for the literature review. Primary technical success was 91.69% (95% CI: 85.34–97.24%). Mean percentage of permanent paraplegia was 5.27% (95% CI: 3.55–7.01%). Visceral graft patency during the mean follow-up of 27.54 months (95% CI: 17.41–37.66 months) was 94.5% (95% CI: 92.5–96.5%). Mean pooled percentage rate of overall endoleaks during the follow-up period was 16.72% (95% CI: 11.15–22.29%). Analysis revealed 15.32% (95% CI: 11.04–19.61%) of 30- day/in-hospital mortality and 65.98% (95% CI: 58.15– 73.81%) of overall survival after the follow-up period. Conclusion. Although thought as less invasive, the hybrid ThAAA repair is still associated with a considerable morbidity and mortality. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 175008]